Lower cortical thickness index does not correlate with increased surgical complications in proximal femoral fractures: a clinical and radiological study - Method Kabelitz; Manuel Waltenspül; Michael Dietrich (Scientific Reports)
Abstract The cortical thickness index (CTI) is a radiological measure and correlates with diminishing local bone quality in the proximal femur. The objective of this study was to assess the association between a lower CTI and the occurrence of peri- and postoperative surgical complications. A total of 228 consecutive patients treated with endomedullary nailing for trochanteric fracture (TFx) (AO/OTA 31A1.1–31A2.3) (n = 99) and hemi-/total hip arthroplasty for femoral neck fracture (AO/OTA 31B1–B3) (FNFx) (n = 129) with a mean age of 82 ± 9.9 (50–99) years were retrospectively reviewed. An evaluation of these cases was conducted to ascertain the presence of any surgery-related complications. Eighteen patients (7.9%) undergoing revision surgery were identified. Patient demographics and radiographic measurements of these groups were compared to the cases without complications (n = 210) and statistically analysed. A total of 18 patients (7.9%) with complications who underwent revision surgery were identified. Among the total number of patients, 10 (55.6%) exhibited mechanical complications. The remaining patients underwent a subsequent revision due to infection (n = 4), seroma/hematoma (n = 3), or a running wound (n = 1). The FNFx group exhibited a lack of intraoperative fractures; however, two periprosthetic fractures occurred subsequent to another fall (36 and 59 days postoperatively). A total of five incisions or extractions of the helical blade were identified in the TFx group. The following factors contributed to the necessity for revision: tractus irritation (n = 2), one intraoperative fracture, one running wound, and one seroma. Among all of the variables that were analyzed, including age, body mass index, and hemoglobin level, only the CTI of the affected side in the TFx group was found to be significantly higher in the complications group, as well as the mechanical complications group (0.51 ± 0.09, 0.58 ± 0.05, 0.58 ± 0.05; p = 0.029). Poor local bone quality, as indicated by a low CTI, is not associated with increased complication rates following surgically managed proximal femoral fractures. Instead, the predominant contributors to mechanical complications seem to emanate from alternative factors, such as insufficient fracture reduction and suboptimal blade positioning.